Impact of the revised CLSI M100 (36th edition, 2026) minimum inhibitory concentration breakpoints on antimicrobial susceptibility interpretation and multidrug-resistance classification of clinical Pseudomonas aeruginosa isolates: a retrospective study - Maxmillando Rymbai; Vedant Vikrom Borah (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Susceptibility interpretation depends on the breakpoint applied to the measured minimum inhibitory concentration (MIC). The CLSI M100 36th edition (2026) introduced revised criteria for Pseudomonas aeruginosa, including lower fluoroquinolone breakpoints, removal of the gentamicin breakpoint, restriction of amikacin reporting to urinary isolates and removal of the colistin-susceptible category. Authors assessed how reinterpreting archived MICs altered susceptibility categorisation and multidrug-resistant (MDR)/extensively drug-resistant (XDR) classification. Methods: Archived VITEK-2 MIC results for 200 non-duplicate clinical P. aeruginosa isolates (December 2020–January 2025) were interpreted twice using the laboratory’s previously reported interpretations and the 2026 CLSI criteria. Categorical agreement, susceptibility percentages (Wilson 95% CIs) and MDR/XDR proportions (Magiorakos framework) were compared and paired changes were tested using the exact McNemar test. Results: Of the 1,871 drug–isolate results interpretable under both schemes, 285 (15.2%) changed categories. According to the 2026 criteria, susceptibility ranged from 35.8% (levofloxacin) to 54.1% (piperacillin/tazobactam). Reinterpretation resulted in increased susceptibility for several β-lactams and ciprofloxacin, mainly through resistant-to-susceptible reassignment (McNemar p≤0.015). Colistin lost its susceptible category, leaving 91.9% intermediate and 8.1% resistant strains, without any MIC changes. Overall, 38.5% of the isolates were non-MDR, 10.0% were MDR and 51.5% were XDR strains. Conclusions: Under CLSI M100 36th edition, reinterpretation reclassified roughly one in seven results, with a net susceptibility gain for several β-lactams and ciprofloxacin and removal of the colistin susceptible category, while most isolates remained XDR. Laboratories should revalidate these breakpoints and account for colistin and aminoglycoside reporting changes in the antibiograms.